(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
In this document an epistemological analyst, about the concept similarity will be done, by identifying ruptures and affiliations that have been resistant to evolution, the widespread and therefore, could be described as epistemological obstacles. Moreover, the distinction of the three stages of analysis regarding the evolution of the concept of similarity has allowed systematize three approaches to the concept when considered as a teaching object.